SYNTHESIS AND CHARACTERISTICS OF BIODEGRADABLE FILMS BASED ON AGAR (Ecological Bulletin of Kryvyi Rih District, 2024)
A wide range of properties, along with economic availability, have made products made of polymer materials an integral part of all areas of our life. The rapid growth rate of the production of artificial and synthetic polymers and the short "useful life" time for a significant part of them have put humanity in front of a serious problem of the accumulation of plastic waste and its negative impact on the environment, especially on living nature. Banning the use of thin and ultra-thin films slows down the rate of plastic pollution, but does not solve the problem as a whole. In addition, in some cases there is no acceptable alternative to replace their use. Therefore, one of the ways to solve this problem is to replace harmful plastics in mass-use products (bags, packaging films, etc.) with those that have similar properties, but are harmless to the environment, namely, capable of decomposing in a much shorter time and not to form harmful substances. Today, several types of biodegradable plastics are widely used, but not all of them are completely safe for the environment, so the search for safe plastic has not lost its relevance. The article analyzes normative and scientific materials on the topic of synthesis, properties and use of biodegradable films, gives the results of the study of film formation processes in the system: agar-agar - glycerol - sap of plants of the Euphorbia family, and proposed methods of synthesis of three types of films of different composition. A set of properties was established for all obtained films: tensile strength, relative elongation, permeability to moisture, solubility in neutral, acidic and alkaline solutions, and their comparative characteristics were given. The perspective of further studies of films of this composition for their practical use is shown.
Keywords: plastic, biodegradable films, bioplastic, agar-agar, biodegradable polymers